Dampak penggunaan beluntas dalam upaya menurunkan kadar lemak daging terhadap produksi dan kadar lemak telur itik lokal - . Rukmiasih; A. S. Tjakradidjaja; . Sumiati; H. Huminto (Institut Pertanian Bogor, 2009)
The beluntas (Piuchea indica L) leaf powder is one of the herbs species which contains antioxidants (flavonoid, vitamin C and beta-carotene), phytochemical and antinutrients. This study was designed to know the ability of the beluntas on the sensory of meat and duck egg without gave the negative effect on duck performances. The results showed that off-flavor's skinned meat duck were not affected, while off-flavor's duck and salted duck eggs are significantly reduced by 0.5% and 1% of beluntas leaf meal in the feed ration. Fatty acids of yolk eggs and duck meat were higher by giving beluntas leaf meal on the ration than without giving one. This showed that antioxidant on beluntas leaf meal could prevent lipid oxidation. TBA value of duck meat was the lowest by giving 0.5% of beluntas on the ration. The productivity such as egg production and feed conversion were the best by giving 1 °/o of beluntas leaf meal on the ration. Egg weight, quality of eggs; fat and cholesterol of yolk were not affected. A higher nutrient digestibilities (protein, energy, Ca and P) was obtained in duck eating 1.0% beluntas leaves (Psmall intestines. The numbers of ducks experiencing liver damage were the lowest in ducks consuming 1.0% beluntas leaves than those eating 0.5% beluntas